Synergy of Administrative Law and Criminal Law in Combating Corruption in Indonesia: Sinergi Hukum Administrasi dan Hukum Pidana Dalam Penanggulangan Korupsi di Indonesia - Saraya Nurhadi, Sitta; Winjaya Laksana, Andri; Lailiyah, Kusroh; Handayani, Yusrina (Mendapo: Journal of Administrative Law, 2025)
The importance of synergy between administrative law and criminal law in overcoming corruption is that administrative law has a preventive and corrective role through internal supervision mechanisms and administrative sanctions, while criminal law is present repressively to prosecute violations that have fulfilled the elements of a crime with the criminal justice system. The increasing number of corruption cases in Indonesia shows that the weaknesses in the administrative system are opening up loopholes for corruption to occur. The lack of integration between the two legal systems causes ineffectiveness in early detection and law enforcement in Indonesia. This article recommends regulatory updates, strengthening coordination between institutions, and building an integrated information system as strategic steps towards more effective and equitable corruption eradication. This article analyzes the synergy of state administrative law and criminal law in overcoming corruption in Indonesia, evaluates the synergy practices that have been running, and offers a more effective and efficient legal collaboration model through efforts to synergize state administrative law and criminal law in overcoming corruption in Indonesia. With a juridical-normative approach and case studies, it is hoped that this study can contribute to strengthening the national legal system that is oriented towards the principles of clean and authoritative governance.